Cell behavior under hypoxic conditions. Computational 3D model - Urdeitx Diaz, Pau; Doweidar, Mohamed H.; Jamaleddin, Seyed Mousavi (Jornada de Jóvenes Investigadores del I3A, 2019)
During the early stages of bone regeneration, oxygen plays a key role, recruiting mesenchymal stem cells and regulating the processes of differentiation, proliferation, and apoptosis. To study in these effects, a 3D computational model has been developed, where the effects of oxygen in the mentioned processes are considered.